Prototype of Water Level and Rainfall Detection System as Flood Warning Based On Blynk Iot Application - Faisal, Muhammad; mutiara, zahra; Awwal Miftah Hidayat, Syahrul; Rinaldi Basrida, Ardhy; Fazrin, Mochammad Tedy (Pandawan Sejahtera Indonesia, 2023)
Rainfall in the rainy season can last for about six months, resulting in continuous rain and increasing the amount of water that causes flooding. The community does not directly get information or be informed when it rains. To anticipate these problems, the Prototype of Water Level and Rainfall Detection System as a Flood Warning Based on the Blynk IoT Application is considered effective for developing a rainfall and water level monitoring system. By using the tool design method, flowchart, system analysis (SDLC), and testing using the black box testing method. The system detects the distance between the sensor and the water surface. If the distance to the water level is close to the sensor, the system will report a flood and then switch to the Blynk software. The mobile will display a message and the system can enter all distances into the program.